Discussion on Spontaneous Parametric Down-conversion (SPDC) Based on Parametric Oscillator Model. Issue 1 (March 2021) - Peng, Yu; Wu, Minghe; Chen, Sheng; Fan, Zhibin
Abstract: In this article, we use the theory of simple harmonic motion to estimate the vibration energy of Boron atom. Subsequently we employ the parametric oscillator model to discuss photon pairs with wavelength of 710 nm. When a laser with wavelength of 355nm illuminates the barium meta-borate crystal, parametric resonance could lead to the effect of spontaneous parametric down-conversion.